Subcellular Clearance and Accumulation of Huntington Disease Protein: A Mini-Review - Zhao, Ting; Hong, Yan; Li, Xiao-Jiang; Li, Shi-Hua (Frontiers in Molecular Neuroscience, 2016)
Huntington’s disease (HD) is an autosomal dominant, progressive neurodegenerative disease caused by an expanded polyglutamine (polyQ) tract in the N-terminal region of mutant huntingtin (mHtt). As a result, mHtt forms aggregates that are abundant in the nuclei and processes of neuronal cells. Although the roles of mHtt aggregates are still debated, the formation of aggregates points to deficient clearance of mHtt in brain cells. Since the accumulation of mHtt is a prerequisite for its neurotoxicity, exploring the mechanisms for mHtt accumulation and clearance would advance our understanding of HD pathogenesis and help us develop treatments for HD. We know that the ubiquitin-proteasome system and autophagy play important roles in clearing mHtt; however, how mHtt preferentially accumulates in neuronal nuclei and processes remains unclear. Studying the clearance of mHtt in neuronal cells is a challenge because neurons are morphologically and functionally polarized, which means the turnover of mHtt may be distinct in different cellular compartments. In this review, we discuss our current knowledge about the clearance and accumulation of mHtt and strategies of examining mHtt clearance and accumulation in different subcellular regions